Economic socialization program in business management and trust relationships in people from urban and rural areas in Caraz, Huaylas, Ancash - Paredes Tarazona, Mildred (2013)
Experimental research, quasi-experimental design that aims to observe the effect of economic socialization program on the management of production units and business relationships of trust in a group of 24 volunteers over 18 years old from urban and rural area of Caraz. Was diagnosed and trained on the principles of administration: Management, Coordination, Organization, Planning, and Communication. Measurement was made before and after the disposition towards trust relationships in the business, with a Likert scale of four factors: a) Competition b) Concern for the other, c) Equity, d) View of himself. The reliability of the instrument was 0.74 and validity established by the method of content. We found 47% in business management skills, emphasizes the principle of Organization and Management, in contrast with low values in the dimensions of Evaluation, Development Strategies and Objectives. It is a high tendency in the willingness to trust and have confidence in a partner, who only enhances by Competition Factor and decreases by a factor of Equity because of Economic Socialization Program for relations of trust in residents of urban and rural partners Caraz, Huaylas, Ancash.